Photoresponsive hydrogel system for ultraviolet (UV)controlled drug delivery: A mini review - Fatin Ayu Kartika, Mohd Suzaki; Norazlianie, Sazali; Afdhal, Junaidi; Mimi Sakinah, Abdul Munaim; Noor Azizah, Sidek; Wan Norharyati, Wan Salleh; Norsuhailizah, Sazali (Penerbit UMP, 2025)
This review offers adepth examination of the latest developments in UV light-responsive hydrogels, emphasizing their role as advanced platforms for drug delivery, especially considering wound care and topical treatments. Thediscussion showshow photochromic compounds such asazobenzene, spiropyran, and spirooxazine are incorporated into hydrogel structures. These integrations assist precise and controllable drug release when exposed to UV light. The mechanisms involvedin this process are analyzed throughthe behaviourlike photoisomerization-induced swelling, alterations in porosity, and reversible molecular conformations. The comparison between UV-responsive hydrogels and traditional counterparts emphasizes their superior ability to offer spatial and temporal control, targeted therapy, and minimized side effects. The review critically evaluates various characterization techniques—including swelling tests, FTIR, UV-Vis spectroscopy, SEM, mechanical evaluations, and rheological assessments—to understand how these materials behave before and after UV exposure. Besides, the discussion addresses environmental sustainability, economic viability, and manufacturing scalability, acknowledging current challenges and proposing potential solutions for future innovation. Concluding with prospective research directions, the paper emphasizes advancements in dual-stimulusresponsive hydrogels, alternativeresponsive to visible or near-infrared light, and the development of intelligent wearable patches. Overall, UV-responsive hydrogels demonstrate major promise as the next generation of drug delivery systems, particularly in wound management, though concerns regarding safety, biodegradability, and commercial translation still need to be addressed.